2016
DOI: 10.1016/j.comppsych.2015.07.008
|View full text |Cite
|
Sign up to set email alerts
|

First empirical evaluation of the link between attachment, social cognition and borderline features in adolescents

Abstract: The study provides the first empirical evidence of well-established theoretical approaches to the development of BPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
74
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 56 publications
6
74
0
3
Order By: Relevance
“…Furthermore, the association between attachment security and mentalization deficit was investigated using an independent measure of mentalization in a sample of 259 adolescents admitted to an inpatient unit, and findings showed that hypermentalizing was significantly correlated with attachment insecurity, assessed dimensionally as CAI narrative coherence (Sharp et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the association between attachment security and mentalization deficit was investigated using an independent measure of mentalization in a sample of 259 adolescents admitted to an inpatient unit, and findings showed that hypermentalizing was significantly correlated with attachment insecurity, assessed dimensionally as CAI narrative coherence (Sharp et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that romantic dysfunction may be the most notorious example of the longstanding interpersonal impairments observed in individuals with BPD [42] . The study of romantic relationships among people with BPD is of clinical and economic interest as well as theoretical interest.…”
mentioning
confidence: 99%
“…Within close relationships, several studies stress that people with BPD exhibit difficulties in engaging in healthy, romantic relationships when compared with healthy controls or people with other psychiatric diagnoses [42,43] . It has been suggested that romantic dysfunction may be the most notorious example of the longstanding interpersonal impairments observed in individuals with BPD [42] .…”
mentioning
confidence: 99%
“…Recently, several studies have also started to examine the RF"s putative mediation role linking insecure adolescent or adult attachment to BPD symptom expression (Carlson, Egeland, & Sroufe, 2009;Fossati et al, 2009;Fossati, Feeney, Maffei, & Borroni, 2011, 2014Sharp, Venta, et al, 2016). Fossati and colleagues provided three cross-sectional studies carried on community samples, examining the relationships between avoidant and anxious attachment dimensions and conceptual cousins of RF processes (i.e.…”
mentioning
confidence: 99%
“…preoccupied and fearful), is related to BPD diagnosis via alexithymia features, namely difficulties in describing and being aware of ones" own feelings, thereby hinting to impairments in RF. Finally, based on a multiple mediational approach, Sharp et al (2016) investigated the cross-sectional interplay between attachment, objective performance to a socio-cognitive task, self-reported emotion regulation and borderline features in a sample of 259 adolescent inpatients. They observed that, unlike emotion dysregulation, excessive RF capacities independently mediated the relation between attachment insecurity and level of BPD features in adolescence.…”
mentioning
confidence: 99%